Pre-arrest administration of the cell-permeable free radical scavenger tempol reduces warm ischemic damage of lung function in non-heart-beating donors - Hodyc, Daniel; Hnilickova, Olga; Hampl, Vaclav; Herget, Jan (The Journal of heart and lung transplantation, 2008)
BACKGROUND: Lungs retrieved from non-heart-beating donors (NHBDs) may alleviate the shortage of suitable organs for transplantation. The critical point is the preservation of lungs during warm ischemia, when severe damage is caused by free radicals. We investigated the effect of ventilation, pre-arrest administration of heparin, and the cell-permeable free radical scavenger, tempol, on the function of NHBD grafts. METHODS: Six experimental and two control groups (n = 6 per group) were established. All experimental groups underwent a protocol of NHBD lung harvesting, which included 1 hour of warm ischemia after pentobarbital euthanasia followed by 90 minutes of cold ischemia. The groups were constructed as follows: Group An-non-ventilated during warm ischemia, no heparin; Group Av-room-air ventilated during warm ischemia, no heparin; Group Hn-non-ventilated, heparin added pre-arrest; Group Hv-ventilated, heparin; Group Tn-non-ventilated, heparin and tempol added pre-arrest; Group Tv-ventilated, tempol, heparin; Group Ac-control group, no warm and cold ischemia, lungs harvested immediately after euthanasia; and Group Tc-controls with tempol added pre-arrest. The lungs were then perfused ex vivo and the perfusion pressure, lung weight and arteriovenous difference in oxygen partial pressure were measured. RESULTS: We found that room-air ventilation during warm ischemia caused severe pulmonary edema during reperfusion. Heparinization prevented an increase in perfusion pressure and ameliorated the oxygen transport ability. Pre-arrest administration of tempol prevented edema formation after ventilation during warm ischemia and had a positive effect on the oxygen transport ability of the lungs. CONCLUSIONS: The free radical scavenger tempol, which has a very good ability to permeate biologic membranes, contributes to better preservation of lungs retrieved from NHBDs.
Keywords: dárci tkání; krysa rodu Rattus; mužské pohlaví; cyklické N-oxidy; Male; Free Radical Scavengers; srdeční zástava; heparin; Lung Transplantation; plicní ventilace; Warm Ischemia; Organ Preservation; reperfuzní poškození; Time Factors; Heparin; Rats; Anticoagulants; Pulmonary Ventilation; Lung; uchovávání orgánů; antikoagulancia; Animals; scavengery volných radikálů; zvířata; teplá ischemie; Spin Labels; transplantace plic; Tissue Donors; plíce; spinové značení; Heart Arrest; časové faktory; Cyclic N-Oxides; Reperfusion Injury